Civil service reform and structural adjustment - "Das, S. K." (New Delhi, 1998)
Written by a senior civil servant, this book locates civil service reform in India in the context of the ongoing structural adjustment program. The challenge of constructing an agenda for India is that while the civil servant ought to be given the necessary autonomy to function and be effective, that autonomy should be subjected to a defined system of accountability to direct the agenda toward collective aims. Besides presenting attempts in developing and developed countries, it discusses the background, current status and possible reforms, and the acceptability of reforms in India.
Keywords: Civil servants -India -Biography